THE EFFECT OF CAREER TRAINING AND DEVELOPMENT ON EMPLOYEE PERFORMANCE AT PT. POST INDONESIA (PERSERO) YOS SUDARSO BRANCH, CIREBON - Dede Ibrahim Maulana; Eko Prasetyo (Politeknik Mardira Indonesia, 2025)
This study aims to analyze the effect of training and career development on employee performance at PT. Pos Indonesia, Yos Sudarso branch. The research method used was associative sampling. The sampling technique used was saturated sampling, with a sample size of 79 respondents. The questionnaire met the instrument test and the classical assumption test. The results indicate that training has a positive and significant effect on employee performance, with a correlation coefficient (R) of 86.7%, categorized as very strong, and a coefficient of determination (R2) of 75.1%. Career development has a positive and significant effect on employee performance, with a correlation coefficient (R) of 34.7%, categorized as moderate, and a coefficient of determination (R2) of 12.1%. 3. Training and career development collectively have a positive and significant impact on employee performance, with a correlation coefficient (R) of 88.0%, categorized as very strong, and a determination coefficient (R2) of 76.8%. The remainder is influenced by other variables not examined.